Frozen Planet : A World Beyond Imagination - Fothergill, Alastair and Berlowitz, Vanessa; Foreworded by Attenborough, David (Ebury Publishing, 1988)
Frozen Planet is the follow-up to the ground-breaking Planet Earth and has been created by the same award-winning team. Most of us will never travel to these great wildernesses and, even for those lucky enough to have gone, this portrait of our polar regions will surprise and astound. The Ice Worlds episode of Planet Earth attracted the most viewers and this series picks up where it left off. The Antarctic landmass and Arctic Ocean see the most extreme changes of climate on our planet. From the Great Melt in Spring to the 24-hour summer, the beginning of the Big Freeze and long dark winter, this epic series will follow the dramatic landscapes and the emotional life stories of the animals that live there.
Include Colour Illustrations and Index
Keywords: Polar regions -- Animals -- Adaptation (Biology)